PENGEMBANGAN MODEL EVALUASI PEMBELAJARAN SENI BUDAYA SMP - Kun Setyaning Astuti (Universitas Negeri Yogyakarta, 2010)
This study aimed at developing an integrated curriculum of art and culture and developing a model of evaluating art and culture learning at Junior High Schools (SMP). This study was a Research and Development study consisting of some stages, i.e. survey, designing instrument, testing the instrument, drafting the model of evaluating art and culture learning, limited and extended validation for the model, implementation, and analysis of the effectiveness of the model. This study made use the experimental method with pre-test and post-test. Data analysis was carried out using multilevel analysis. The results of the study are: 1) the development of integrated curriculum puts the emphasize more on the integration of learning material for art and culture subject rather than on the curriculum; 2) the appropriate evaluation model of learning art and culture should contain: Context, which is based on the previous competency and the school cultural environment, Learning Design, which is based on the descriptions of context and target; Implementation and Monitoring, which are carried out continuously; Product Measurement which includes the cognitive, psychomotor, and affective aspects; Decision Making, which is based on the product, and Recommendation in the form of learning that concerns imitation, creation, or originality